La citoyenneté européenne : signification et perspectives dans le cadre du traité d'Amsterdam (Note) - Jean, Cynthia (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
Since the objective of the European Union is to be closer to Us citizens, the Treaty of Amsterdam contributes to the development and the significance of the European citizenship. Through a neo-liberal perspective, it strengthens, in both national and community levels, the compromise between democratic values, such as social justice and equity principle, and economic liberalism. While the social dimension of the European citizenship is reinforced, the specific rights provided only to Union's citizens are, however, marginalized. In order to explain this situation, the paper will first present the implications of the European citizenship, and then, analyze the main provisions of the draft treaty related to a stronger relationship between the Union and Us citizens.